Treatment of Dry Eye With Intracanalicular Injection of Hydroxybutyl Chitosan: A Prospective Randomized Clinical Trial - Lin, Tong; Wang, Wushuang; Lu, Yang; Gong, Lan (Frontiers in Medicine, 2021)
Background: Punctal/intracanalicular plugs on the market nowadays are all designed before clinical use in treating dry eye disease (DED). To provide an individualized lacrimal drainage system occlusion method and reduce the complications, we developed a ‘liquid plug’ strategy by intracanalicular injection of hydroxybutyl chitosan (HBC) solution, a thermosensitive, phase-changing biomaterial. This study evaluated the efficacy and safety of HBC plug in treating dry eye disease, compared with the VisiPlug absorbable intracanalicular plug. Methods: A monocenter, randomized, control clinical trial was performed. 50 patients with DED were randomized 1:1 to undergo either the HBC injection treatment or the VisiPlug treatment. Ocular Surface Disease Index (OSDI) questionnaire, tear break-up time (TBUT), corneal fluorescence staining (CFS), tear meniscus height (TMH) and phenol red thread test were evaluated at Day 0 (baseline, before treatment), Week 1, Week 4 and Week 12. Results: The two groups had a balanced baseline of age, sex and DED related characteristics. Both occlusion methods could relieve the symptoms and signs of DED. Significant improvement was found in OSDI, phenol red thread test and tear meniscus height (P<0.05 compared to baseline) but not in corneal fluorescence staining and tear break-up time (P>0.05). There is no statistically significant difference between HBC injection and VisiPlug at Week 1&4 (P>0.05). However, at week 12, the HBC injection was not as effective as the Visiplug in maintaining phenol red thread test (HBC: 5.35±3.22mm, VisiPlug: 8.59±4.35mm, P=0.009) and tear meniscus height (HBC: 206.9±47.95μm, VisiPlug: 242.59±60.30μm, P=0.041). The numbers of ocular adverse events were relatively low in both groups. Conclusions: The HBC injection showed a similar efficacy and safety compared to VisiPlug. The intracanalicular injection of HBC solution proves to be a promising, individualizing method to treat DED. Clinical Trial Registration: This study is registered with Chinese Clinical Trial Registry (https://www.chictr.org.cn/enindex.aspx), Identifier: ChiCTR1800016603.